Proteomic Profiling and Monitoring of Training Distress and Illness in University Swimmers During a 25-Week Competitive Season - Knab, Amy M.; Nieman, David C.; Zingaretti, Laura M.; Groen, Arnoud J.; Pugachev, Artyom (Frontiers in Physiology, 2020)
PURPOSE: To evaluate relationships of proteomics data, athlete-reported illness, training distress (TDS), and coaches’ ratings of distress and performance over the course of the competitive season. METHODS: Thirty-five NCAA Division II swimmers were recruited to the study (male n=19, female n=16; age 19.1±1.6 y). Athletes provided fingerprick dried blood spot (DBS) samples, illness symptoms, and TDS every Monday for 19 of 25 weeks in their season. Coaches monitored performance and rated visual signs of distress. DBS samples were analyzed for a targeted panel of 12 immune-related proteins using liquid chromatography/mass spectrometry (LC/MS). RESULTS: Thirty-two swimmers completed the protocol. The data were grouped in 2-3 week segments to facilitate interpretation and analysis of the data. TDS scores varied between athletes, and were highest during the early fall conditioning ramp up period (8.9±1.6 at baseline to a peak of 22.6±2.0). The percent of athletes reporting illness was high throughout the season (50% to 78%). Analysis of TDS using Principle Component Analysis (PCA) revealed that 40.5% of the variance (PC1) could be attributed to illness prevalence, and TDS scores for the athletes reporting illness and no illness were significantly different across the season (P<0.001). The coaches' ratings of swim performance and swimmer's distress, sex, and racing distance (sprinters, middle distance, long distance) were not correlated with PC1. Linear Discriminant Analysis (LDA) analysis of the data showed a significant separation of the baseline weeks from exam weeks with or without competitions, and with competitions alone (p<0.001). Most of the 12 proteins monitored over the course of training were upregulated, and the addition of the protein data to LDA analysis enhanced the significance of the separation between these groups of weeks. CONCLUSIONS: TDS and illness were significantly related in this group of 32 collegiate swimmers throughout the competitive season, and expression of immune proteins improved the statistical separation of baseline weeks from the most stressful weeks. TDS data provided by the swimmers did not match their coaches' ratings of distress and swim performance.